A Model for Defining the Concept and Practice of Translation, from the Perspective of Greimassian Semiotics - Troqe, Rovena (TTR)

(untitled) (Association canadienne de traductologie, 2016)
In this study, a new model of translation as a general theoretic concept and as a social practice is outlined, drawing form Greimassian semiotics. As a theoretic concept, translation is defined by the Semiotic Square of Translation as the emergence of the general category self coming into being in relation to the category non-self, through the semio-logic operations that correlate the immanent concepts, equivalence and difference. As a social practice, translation arises from the contractual interaction between two actants, the Initiator and the Translator, which operate through acts of manipulation, performance and sanction. This theoretical framework is applied to the study of a parallel corpus.